Formes et perceptions des collaborations entre enseignants-chercheurs des ENSA - Rachel Metzger; Jérôme Eneau; Jacques Audran (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Since 1968, architectural education in France has undergone a series of reforms, not only in terms of governance, but also regarding teaching and the status of teachers. Interdisciplinarity (interactions between disciplinary fields, with regards to the organization of knowledge or collaboration between teachers) is at the heart of these interrogations, given the centrality of architectural design in the curriculum leading up to the architect's diploma, as compared to that of more contributory disciplinary fields. What interactions are sought today by teachers of different disciplines, in this system centered on the teaching of architectural design?